The Shaping Mechanisms, Constituent Dimensions, and Practical Pathways of College Students’ Conceptions of Happiness in Non-Ethnic-Minority Regions from the Perspective of Forging a Strong Sense of Community for the Chinese Nation - Zhang, Cai; Tao, Liu (Journal of Educational Research and Policies, 2026)
On the new journey of building a modern socialist country in all respects, forging a strong sense of community for the Chinese nation constitutes the guiding principle of the Party’s ethnic work in the new era and a strategic thread through which universities fulfill their fundamental task of fostering virtue through education. As a major force in national development, college students in non-ethnic-minority regions hold conceptions of happiness whose formation concerns not only their individual quality of life but also the effectiveness of building a shared spiritual home for the Chinese nation and safeguarding national ideological security. From the contemporary perspective of forging a strong sense of community for the Chinese nation, this paper examines how such consciousness empowers the conceptions of happiness held by college students in non-ethnic-minority regions through the underlying mechanisms of value isomorphism, spiritual nourishment, and cognitive guidance. It then explains the structural progression of these conceptions from an unreflective state to conscious self-direction across the dimensions of emotional resonance, value cognition, and behavioral practice. On this basis, it proposes cultivation pathways that include establishing a comprehensive ideological and political education system, creating an immersive cultural environment, and building practice platforms that integrate knowledge and action. By jointly developing theoretical logic and practical strategies, the paper seeks to guide college students in non-ethnic-minority regions to locate an appropriate coordinate for happiness within the grand narrative of the community for the Chinese nation, thereby bringing individual development into resonance with the destiny of the country.